Climatic trends and potato late blight risk in the upper Great Lakes region of the USA - Baker, Kathleen M; Kirk, William W; Stein, Jeffrey M; Andresen, Jeffrey A (MTT, 2007)
Concern in the agricultural community over observed and projected climate change has prompted numerous studies on the possible implications for crop yields. However, relatively little work has focused on disease management. In the upper Great Lakes region of the United States, late blight (Phytophthora infestans) of potato (Solanum tuberosum) is a temporally sporadic disease, occurring only when microclimate conditions within the canopy are favorable and inoculum is present. This and other studies indicate that historical climatological trends in the upper Great Lakes region have resulted in warmer and wetter growing season conditions, as well as local increases in precipitation totals and in the frequency of days with precipitation. Consequently, the risk of potato late blight is increasing. Historical trends in hourly weather variables and potato late blight risk as expressed by a modified Wallin disease severity value index were analyzed at seven regional weather stations from 1948 99. All sites showed significant trends in at least one of the risk estimates. While late blight risk was greatest at all locations in August, periods of increasing risk occurred across the region particularly during July. The increases in disease risk appeared to be associated with upward trends in dry bulb and dew point temperature at nearly all of the stations, especially during July and August. Increased risk of potato late blight has implications for extension agents and commercial horticulturists that include increased emphasis on grower education and application of integrated disease management techniques.
Keywords: Ka